(untitled) (Journal of Kidney Cancer, 2025)
Von Hippel–Lindau (VHL) syndrome is an autosomal dominant hereditary tumor syndrome caused by mutations in the VHL gene. It is characterized by the occurrence of tumors in multiple organs. Pancreatic involvement in VHL syndrome can present as pancreatic cysts or neuroendocrine tumors, which may interfere with both pancreatic exocrine and endocrine pancreatic functions. To our knowledge, no patients with VHL syndrome complicated by diabetes mellitus, pulmonary nodules, and thyroid nodules are reported in the literature. This study aims to explore the pathogenesis of diabetes, pulmonary nodules, and thyroid nodules in VHL syndrome through the analysis of a patient with VHL syndrome and to review relevant literature.